Gardner's syndrome: a case report and review of the literature. - Fotiadis, C; Tsekouras, D-K; Antonakis, P; Sfiniadakis, J; Genetzakis, M; Zografos, G-C (World J Gastroenterol, 2005)
Gardner's syndrome is an autosomal dominant disease characterized by the presence of colonic polyposis, osteomas and a multitude of soft tissue tumors. The syndrome may present at any age from 2 mo to 70 years with a variety of symptoms, either colonic or extracolonic. We present a case of a 11-year-old female patient with Gardner's syndrome who presented with a lumbar area desmoid tumor and treated with resection of the desmoid, restorative proctocolectomy and ileal pouch anal anastomosis, A review of the current literature has been performed.
Keywords: Child; Colonic Pouches; Desmoid Tumors; Female; Gardner Syndrome; Humans; Proctocolectomy, Restorative